Challenges in the technological adoption of document management systems - Sussy Bayona-Oré; Marlene Reyes (Universitas Ahmad Dahlan, 2025)
Incorporating information and communication technologies (ICT) in public organisations in keeping with digital government policies and access to ICT by citizens motivates public institutions to implement systems to provide better services to citizens. One of the most essential public services is the documentary process, which includes document management systems (DMSs) storing, organising, and managing the documentary flow. The acceptance and use of a DMS enabling digital signature in public institutions depends to a certain extent on a set of factors influencing user behaviour towards it. This paper reports the findings of a quantitative, cross-sectional, and correlational study examining the behavioural intention (BI) to use a DMS, employing three constructs of the unified theory of acceptance and use of technology (UTAUT). The research involved 998 workers from public institutions who participated in a survey, with quantitative data analysed using Spearman correlation. The results show that performance expectancy (PE), effort expectancy (EE), and social influence (SI) positively correlate with the BI to use a DMS and thus must be considered as relevant factors in DMS implementation in public institutions. The results provide relevant information to policymakers and DMS managers to promote the adoption of DMS in the digital transformation process that organisations are experiencing.